Development of the college student life satisfaction scale (CSLSS): initial validation among Filipino college students - Masagca, Ramon Paulo E. (Frontiers in Psychology, 2025)
Few domain-specific satisfaction measures explicitly evaluate students’ satisfaction with their learning experiences. Although numerous instruments are available to measure student satisfaction, they often focus on general life domains rather than specific aspects of the learning experience. Furthermore, it is imperative to ensure that these measures effectively capture learning experiences, particularly within the context of Filipino college students. The development of the College Student Life Satisfaction Scale (CSLSS) addresses the need for a culturally relevant instrument that reflects the unique learning experiences of this population. It also considers the impact of changes in higher education during the COVID-19 pandemic, emphasizing the importance of school-life balance as a key aspect of student life satisfaction. The CSLSS comprises five dimensions: Peers, Faculty, School Environment, Academic Performance, and School-Life Balance. These dimensions were validated through exploratory factor analysis using responses from n = 406 Filipino college students enrolled in the academic year 2024–2025. The final version of the CSLSS, validated with a sample of n = 327, was found to be a reliable and valid measure of student life satisfaction. It exhibits concurrent validity with the College Satisfaction Scale and the Multidimensional Student Life Satisfaction Scale, and its construct validity is demonstrated through significant correlations with the Academic Hope Scale and the Satisfaction with Life Scale. While objective assessments are essential for informing educational reform, the inclusion of students’ subjective experiences provides critical insights. The integration of both approaches supports a more comprehensive strategy for enhancing educational quality.